Impact of Chlorophyll Shading on the Peruvian Upwelling System. Issue 19 (7th October 2021) - Echevin, V.; Hauschildt, J.; Colas, F.; Thomsen, S.; Aumont, O.
Abstract: The influence of chlorophyll shading on ocean dynamics has been usually disregarded in eastern boundary upwelling systems modeling studies in spite of their very high primary productivity. Here, we study how this effect impacts on the Peru upwelling system using a regional mesoscale‐resolving physical biogeochemical coupled model. We show that the shading effect leads to a surface cooling of up to 1°C on the shelf due to subsurface cooling of the source waters during their transit toward the shelf. The shading effect leads to a more realistic subsurface stratification, a slowdown of the alongshore currents, and a shoaling of the oxycline. Impacts on the regional model biases show that the shading effect needs to be taken into account in both physical and coupled physical‐biogeochemical regional models of upwelling systems. Plain Language Summary: The chlorophyll pigments of phytoplankton capture the downward penetrating solar energy to produce photosynthesis and warm the surface of the ocean. However, this effect is seldom taken into account in ocean models, in particular in upwelling systems where chlorophyll concentration is very high. In this study, we show that taking into account this effect in a model of the Peruvian upwelling system, one of the most productive systems in the world, modifies not only the temperature, circulation, and turbulence, but also stimulates nearshore phytoplankton production and deoxygenation over the shelf. This study shows that this effect needs to be parameterized in future modeling studies. Key Points: The influence of surface chlorophyll shading on the Peru upwelling system is investigated using a physical biogeochemical coupled model The shading effect leads to surface cooling, nutricline and oxycline shoaling, and phytoplankton increase on the shelf The shading effect should be taken into account in high‐resolution eastern boundary upwelling System models